1991
DOI: 10.21273/jashs.116.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Cold Hardiness of Various Provenances of Flame, Roseshell, and Swamp Azaleas

Abstract: Florets of eight provenances representing three native North American azalea species [Rhododendron calendulaceum (Michx.) Torr., R. prinophyllum (Small) Millais, and R. viscosum (L.) Torr.] being grown in Burlington, Vt., were compared during three seasons for cold hardiness by laboratory freezing during cold acclimation. There was a large variability in the number of florets killed within an inflorescence in response to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Several previous studies have indicated that warming stem and floral tissues before low-temperature tolerance testing drastically decreases tolerance. Pellett et al (1991) showed a positive correlation between minimum survival temperature and daily mean temperatures for the 3 days immediately before testing. They indicated that this short-term dehardening maybe more important than ecotype in determining low-temperature survival in certain Rhododendron species.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Several previous studies have indicated that warming stem and floral tissues before low-temperature tolerance testing drastically decreases tolerance. Pellett et al (1991) showed a positive correlation between minimum survival temperature and daily mean temperatures for the 3 days immediately before testing. They indicated that this short-term dehardening maybe more important than ecotype in determining low-temperature survival in certain Rhododendron species.…”
Section: Resultsmentioning
confidence: 90%
“…The LST designated in this report is the lowest temperature treatment that resulted in 100% stem or flower primordia survival. Some previous reports on cold hardiness of woody taxa have reported LST based on survival percentages ranging from 40% to 66% (Biermann et al, 1979;Pellett et al, 1991;Sakai et al, 1986). For our study, 100% survival was chosen because it requires less interpolative manipulation of data to estimate the value, and it does not assume linearity of response to the temperature treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Pellett and Holt (1981) reported on laboratory cold-hardiness limits of several evergreen rhododendron cultivars. Pellett et al (1991) surveyed several native populations of R. calendulaceum, R. prinophyllum, and R. viscosum for cold hardiness. Flowering characteristics and fall foliage coloration of these same populations also were reported Alpert 1988, 1989).…”
mentioning
confidence: 99%
“…Pellett et al (1991) found few differences in the hardiness of floral buds associated with latitude or altitude among provenances of R. calendulaceuna, R. p~inophyllum, and R. viscosum. They attributed this apparently negative finding to the practice of obtaining seeds from northern latitudes at low elevations, thereby obscuring the effects of latitude and altitude on frost hardiness (Pellett et al, 1991). In the current study, the seeds of the more frost-hardy R. calendulaceum, R. canadense, R.…”
Section: Dehydrin Analysesmentioning
confidence: 81%
“…Hardiness phenotypes may be fairly uniform within species or may vary due to local adaptations by populations (Howe et al, 2003). Pellett et al (1991) found few differences in the hardiness of floral buds associated with latitude or altitude among provenances of R. calendulaceuna, R. p~inophyllum, and R. viscosum. They attributed this apparently negative finding to the practice of obtaining seeds from northern latitudes at low elevations, thereby obscuring the effects of latitude and altitude on frost hardiness (Pellett et al, 1991).…”
Section: Dehydrin Analysesmentioning
confidence: 95%